Network formations among immigrants and natives - Gil S. Epstein; Odelia Heizler (Institute for the Study of Labor (IZA), 2009)
In this paper we examine possible network formations among immigrants and natives with endogenous investment. We consider a model of a network formation where the initiator of the link bears its cost while both agents benefit from it. We present the model by considering possible interactions between immigrants and the new society in the host country: assimilation, separation, integration and marginalization. The paper highlights different aspects of immigrants' behavior and their interaction with the members of the host country (society) and their source country (society). We found that when the stock of the immigrants in the host country increases, the immigrants' investment in the middlemen increases and the natives may bear the cost of link formation with the middlemen.
urn:nbn:de:101:1-20090622165
Keywords: D85; J15; F22; A14; 300; Network formations; social networks; assimilation and separation; Migranten; Soziale Integration; Soziale Beziehungen; Gesellschaft; Theorie